PENGARUH AKUNTANSI MANAJEMEN TERHADAP PENGAMBILAN KEPUTUSAN PADA PT. SULTRA KENDARI - Suprianto, Hengki; Darmanto, Darmanto; Tabash, Mosab I.; Abdullah, Rudi (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2024)
This study aims to analyse the extent of the influence of management accounting on decision making at Bank Sultra Kendari a Branch. Quantitative descriptive methods, data collection using questionnaire techniques, respondent characteristics using classical assumption regression models, research descriptions using simple linear analysis, T test (Persial) and determination coefficient test (R2). The results management accounting variables had an effect on decision making, which was shown by the results of simple linear regression through the T test, where the results of the T test of the management accounting variable (X) tcount value 19.423> ttable value 2.024 with a significance value of 0.0000 which is below 0.05. Then test the hypothesis H1. From the results of the management accounting analysis method, it shows that there is a significant influence on decision making at Bank Sultra Kendari. The coefficient of determination R Square (???? 2) of 0.908 means that the effect of variable Y (decision making) is 90.8%. The remaining 9.2% (100% - 90.8%) is influenced by other unknown factors and is not included in this regression analysis.